If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 3) = 5(x + 2) Reorder the terms: 3(3 + 2x) = 5(x + 2) (3 * 3 + 2x * 3) = 5(x + 2) (9 + 6x) = 5(x + 2) Reorder the terms: 9 + 6x = 5(2 + x) 9 + 6x = (2 * 5 + x * 5) 9 + 6x = (10 + 5x) Solving 9 + 6x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 9 + 6x + -5x = 10 + 5x + -5x Combine like terms: 6x + -5x = 1x 9 + 1x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 9 + 1x = 10 + 0 9 + 1x = 10 Add '-9' to each side of the equation. 9 + -9 + 1x = 10 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 10 + -9 1x = 10 + -9 Combine like terms: 10 + -9 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| 3x-8=58 | | 37+26= | | 1b-3b=8 | | X^3+2x^2=15x | | 2x^2+4x+19=0 | | 4x+6=4x+8 | | 4x+20=6x-6 | | 2-6x=5-6x | | 27+x-3x+47=0 | | 5(6x+1)=14x-11 | | -17+5=33 | | -4x-6=5x-6 | | 187-3x=33x+15 | | q+14=8(q+t) | | 0.5x-6=8 | | 8x-4x+7=1 | | 9x-75=6x-12 | | 5(3p+2)-2(4p-3)= | | 3x-1=8x | | ax-2x=a+2 | | 6x^2=7y | | c+2/4=3 | | 20x+6y=y | | 5d+13=2d-5 | | -54=6p-30 | | X-5-.10x=12+.5x | | 2x+5x=7Y+2 | | (X+4)(5x-6)=0 | | kx^2+12+k=0 | | x+45=56 | | -r=-12 | | 2(6-x)=-2(4-x) |